2023
DOI: 10.1007/s00784-023-05202-z
|View full text |Cite
|
Sign up to set email alerts
|

The molecular weight of hyaluronic acid influences metabolic activity and osteogenic differentiation of periodontal ligament cells

Iris Frasheri,
Nikoletta Dimitra Tsakiridou,
Reinhard Hickel
et al.

Abstract: Objective While HA is present naturally in periodontal tissues, its molecular weight can vary widely in vivo. The objective of this study was to directly compare the biological reactions of periodontal ligament cells to four distinct molecular weights of hyaluronic acid (HA). Materials and methods Immortalized human periodontal ligament cells (PDL-hTERT) were cultured for 21 days in culture medium alone (control) or enriched with osteogenic supplements (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A total of 14 articles related to the morphological approach, published between 2013 and 2023 were selected. The human cultured stem cells used for the in-vitro studies include both peripheral blood mononuclear cells (PBMSC) ( Kleinhans et al, 2015 ; Maria et al, 2018 ; Steller et al, 2020 ; Grünherz et al., 2020 ; Zainol Abidin et al., 2023 ) and mesenchymal stem cells (MSc) involved 5 studies ( Maria et al, 2017 ; Hashimoto et al, 2018 ; Liu et al, 2018 ; Ganguly et al, 2020 ; Nugraha et al, 2023 ) whereas periodontal ligament stem cells (PDLSC) ( Di Vito et al, 2020 ; Frasheri et al, 2023 ) and dental pulp stem cells (DPSC) ( Escobar et al, 2020 ; Escobar et al, 2023 ) involved two studies ( Table 3 ). The outcomes of the risk of bias assessment in Table 4 reflect the quality assessment analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 14 articles related to the morphological approach, published between 2013 and 2023 were selected. The human cultured stem cells used for the in-vitro studies include both peripheral blood mononuclear cells (PBMSC) ( Kleinhans et al, 2015 ; Maria et al, 2018 ; Steller et al, 2020 ; Grünherz et al., 2020 ; Zainol Abidin et al., 2023 ) and mesenchymal stem cells (MSc) involved 5 studies ( Maria et al, 2017 ; Hashimoto et al, 2018 ; Liu et al, 2018 ; Ganguly et al, 2020 ; Nugraha et al, 2023 ) whereas periodontal ligament stem cells (PDLSC) ( Di Vito et al, 2020 ; Frasheri et al, 2023 ) and dental pulp stem cells (DPSC) ( Escobar et al, 2020 ; Escobar et al, 2023 ) involved two studies ( Table 3 ). The outcomes of the risk of bias assessment in Table 4 reflect the quality assessment analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies focus solely on the staining of osteoblast differentiation ( Escobar et al, 2020 ; Escobar et al, 2023 ; Ganguly et al, 2020 ; Di Vito et al, 2020 ; Frasheri et al, 2023 ; Zainol Abidin et al., 2023 ; Nugraha et al, 2023 ), three studies only on morphological evaluation methods for osteoclast differentiation ( Kleinhans et al, 2015 ; Steller et al, 2020 ; Grünherz et al., 2020 ) and another four articles involved qualification analysis of both osteoblast and osteoclast differentiation ( Hashimoto et al, 2018 ; Maria et al, 2018 ; Liu et al, 2018 ) ( Table 3 ). All the staining techniques were proven to be successful in evaluating the presence of osteoblast and osteoclast differentiation in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Via binding to its canonical receptors CD44 and RHAMM, it has been shown to increase proliferation, migration, and cell metabolism in periodontal ligament fibroblasts (PDLs), mesenchymal stromal cells (MSCs), and cementoblasts. In osteoblasts and cementoblasts, xHyA may also stimulate the expression of bone-specific genes, while it shifts macrophage polarization towards an anti-inflammatory M2 phenotype (Figure 5) [14,16,[21][22][23][24]. In a recent histomorphometric study in dogs, the combination of a resorbable matrix and xHyA was also shown to be superior, underlining the regenerative capacity of this biomaterial [25].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated the development of an in-situ tissue engineering scaffold (iTE-scaffold) using the coaxial electrospinning technique to sequentially deliver bFGF and BMP-2 [65][66][67][68]. The iTE-scaffold was found to effectively enhance the angiogenesis of periodontal ligament stem cells (PDLSCs) and induce macrophage polarization into the prohealing M2 phenotype, thereby modulating inflammation [7].…”
Section: Novel Findings In Scaffolds Incorporating Growth Factors For...mentioning
confidence: 99%
“…In this regard, the state of the art is that the microenvironment that initiates the generation of tissues supporting teeth is not maintained following tooth development, thereby posing challenges in the restoration of the lost periodontal ligament after reaching maturity [6]. As an advanced technology, the in situ tissue engineering approach, employing biomaterials for controlled delivery adaptable to recapitulating this environment, is considered a promising technology for the treatment of periodontal bone defects [7]. To achieve this objective, numerous biomaterials were established, significantly influencing oral tissue.…”
Section: Introductionmentioning
confidence: 99%